A randomized trial shows dose-frequency and genotype may determine the therapeutic efficacy of intranasal oxytocin. Issue 10 (4th July 2022) - Kou, Juan; Zhang, Yingying; Zhou, Feng; Sindermann, Cornelia; Montag, Christian; Becker, Benjamin; Kendrick, Keith M
Abstract: Background: The neuropeptide oxytocin is proposed as a promising therapy for social dysfunction by modulating amygdala-mediated social-emotional behavior. Although clinical trials report some benefits of chronic treatment, it is unclear whether efficacy may be influenced by dose frequency or genotype. Methods: In a randomized, double-blind, placebo-controlled pharmaco-functional magnetic resonance imaging trial (150 male subjects), we investigated acute and different chronic (every day or on alternate days for 5 days) intranasal oxytocin (24 international units) effects and oxytocin receptor genotype-mediated treatment sensitivity on amygdala responses to face emotions. We also investigated similar effects on resting-state functional connectivity between the amygdala and prefrontal cortex. Results: A single dose of oxytocin-reduced amygdala responses to all face emotions but for threatening (fear and anger) and happy faces, this effect was abolished after daily doses for 5 days but maintained by doses given every other day. The latter dose regime also enhanced associated anxious-arousal attenuation for fear faces. Oxytocin effects on reducing amygdala responses to face emotions only occurred in AA homozygotes of rs53576 and A carriers of rs2254298. The effects of oxytocin on resting-state functional connectivity were not influenced by either dose-frequency or receptor genotype. Conclusions: Infrequent chronic oxytocin administration may be therapeutically most efficient and its anxiolytic neural and behavioral actions are highly genotype-dependent in males.